2014
DOI: 10.9775/kvfd.2013.9894
|View full text |Cite
|
Sign up to set email alerts
|

Çiğ Süt Kalite Değerlendirmesinde Bulanık Mantık Yaklaşımı

Abstract: ÖzetGelişen toplum yapısı ile birlikte gerçek hayatta yaşanılan sorunlar ve olaylara bakış açıları da değişmektedir. İnsanlar sorunlarını sahip oldukları sözel ve sayısal verileri kullanarak çözmekte ve bunun için çeşitli yöntemlerden yararlanmaktadırlar. Matematiksel yöntemler insanlara kesinlik içeren durumlarda sorunların çözümlenmesinde sayısal verileri analiz ederek yardımcı olurken, belirsizlik içeren durumlarda yetersiz kalabilmektedir. Son yıllarda kalite değerlendirilmesi gibi belirsizlik içeren durum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Decision support system has benefited from the work done previously on fuzzy logic [9,12,19,23] , the knowledge and experience of experts, the textbooks on animal breeding [4,31] for decision support system of input variables, the formulation of rules and membership functions of creation. An overview of the system is located in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Decision support system has benefited from the work done previously on fuzzy logic [9,12,19,23] , the knowledge and experience of experts, the textbooks on animal breeding [4,31] for decision support system of input variables, the formulation of rules and membership functions of creation. An overview of the system is located in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this research, expert opinion and a detailed literature review [12,14,18,19,23] Trapezoidal membership function with such as a, b, c and d parameters are expressed as [21,27] . The data that come to system in fuzzy rule base after ready to be processed is processed by inference mechanism according to defined by the form "if-then" rules.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some microorganisms present in the milk adversely affect the quality of milk and dairy products during process of collection, storage, and transportation [3] . This leads to food poisoning and causes economic losses [4] . Studies conducted in Turkey revealed that milk and dairy products are contaminated with enteric bacteria such as Escherichia coli [5] .…”
Section: Introductionmentioning
confidence: 99%